Correlation between inverted maxillary central incisor form and face form in a sample of Sudanese population - Noha Hassan Hussein; Nadia Khaliaf; Mohammed Nasser Alhajj (Wolters Kluwer Medknow Publications, 2016)
Introduction: The selection of artificial teeth is an important concern in complete denture construction. Many theories were developed to objectively select artificial teeth, to simplify the process of choice and to make it more suitable. Objectives: This study was conducted to evaluate the correlation between inverted maxillary central incisors form and face form in a sample of Sudanese population. Materials and Methods: One hundred and sixty-four dental students (138 females and 26 males), with a mean age (20.8 ± 1.81), were randomly selected. Three horizontal distances of the right maxillary central incisor were measured, (cervical width, contact point width, and incisal width). For facial measurements, three horizontal distances on the face were measured, (bitemporal width, bizygomatic width, and bigonial width). Results: Chi-square test was used to estimate the association between face form and central incisor form. No association between tooth form and face form was detected in the study sample (P = 0.092). Conclusion: The findings of our study indicate that this method is not applicable for selection of maxillary anterior teeth in the study sample.